Kaji Eksperimental Rasio Metanol-Bensin Terhadap Konsumsi Bahan Bakar, Emisi Gas Buang, Torsi Dan Daya - Mohamad Rifal; Nazarudin Sinaga (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Methanol (CH3OH) is the one of an alternative fuel for SI engine. Methanol has a similiar charakteristic and fisik properties to gasoline. This study using methanol-gasoline fuel blend (M10, M20 and M40). The aim of this study was to determine the effect of using methanol-gasoline fuel blend of  fuel consumption, exhaust emission, power and torque. In the experiment,  an engine three-cylidre 12 valve with tecnology DOHC Mivec and ECI MPI injection System 1193 cc was used. With a little modification that is using methanol controler to maximize the result of research. The experimental result showed that the fuel consumption decrease with the use of methanol-gasoline ful blend. Each of these reductions in fuel consumption for the M10, M20 and M40 are 1 %, 3% dan 3%. The Power and Torque is increas while using fuel blend than gasoline and it also decrease exhaust emission